Analysis of Regional Original Income, Capital Expenditures and Balancing Funds on Regency/City Economic Growth in East Java Province - Huda, Syamsul; Yuliati, Anik (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The purpose of this research is to determine the influence of Original Local Government Revenue, Capital Expenditures and Balancing Funds on Regency/City Economic Growth in East Java Province. The population that will be observed in this research covers the East Java Province area. This research uses annual data measured in a time series format starting from 2017-2021. The data obtained were analyzed using multiple linear regression analysis. Multiple linear regression analysis is a method used to analyze relationships that have an influence between the independent variable and the dependent variable. Based on the results and discussion as well as the supporting theories explained above, researchers can draw the following broad conclusions: Original Local Government Revenue has a positive effect on Economic Growth in East Java Province. The Capital Expenditure variable has a significant positive effect on Economic Growth. The Balancing Fund variable has a significant positive effect on Economic Growth.